2003
DOI: 10.1562/0031-8655(2003)077<0265:ureoca>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Radiation Exposure of Children and Adolescents in Durban, South Africa¶

Abstract: The solar ultraviolet radiation (UVR) exposure of 30 children and adolescents in three age groups (4-6 years, 7-9 years and 13-14 years) was measured for 1 week in late summer (February-March) in Durban, South Africa, using UVR-sensitive polysulfone film badges (PSFB) attached to the lapel region of the body. The mean and median values for all ages over the study period were 2.0 and 1.2 standard erythemal dose (SED) units, respectively, where 1 SED = 100 J x m(-2). Individual PSFB doses were analyzed as a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 21 publications
1
15
1
Order By: Relevance
“…The results of this study are somewhat different from those of Guy et al (2003), who found 2.8% ambient UVER exposure on the collarbone for 7 to 9 year-olds, during a summer in South Africa. In our study, using children with dosimeters on the shoulder, we obtained 6.7 % for 7 to 8 year-olds.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The results of this study are somewhat different from those of Guy et al (2003), who found 2.8% ambient UVER exposure on the collarbone for 7 to 9 year-olds, during a summer in South Africa. In our study, using children with dosimeters on the shoulder, we obtained 6.7 % for 7 to 8 year-olds.…”
Section: Discussioncontrasting
confidence: 99%
“…Mean ER for primary schoolchildren on summer weekdays tends to lie within a range of between 2.8-4.5% in South Africa (Guy et al 2003), and 4.6% in Australia (Kimlin et al 2001). In another work, in Japan (Ono et al 2005), the weekly mean of daily UV exposure in summer (July) was in a range of 91-170 J/m 2 .…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…During the follow-up period between 1998 -2001, the children acquired overall a median number of 26 MN (IQR ϭ [17,40], range ϭ 1-186). The median number of incident MN was 25 (IQR ϭ [16,38]) for girls and 28 (IQR ϭ [18,42]) for boys (p ϭ 0.003). The number of newly acquired MN was increasing with age (p Ͻ 0.001) (Fig.…”
Section: Description Of Participating Children and Bivariate Associatmentioning
confidence: 99%